Effects of the zeolite framework on the adsorptions and hydrogen-exchange reactions of unsaturated aliphatic, aromatic, and heterocyclic compounds in ZSM-5 zeolite a combination of perturbation theory (MP2) and a newly developed density functional theory (M06-2X) in ONIOM scheme - Boekfa, Bundet (Langmuir : the ACS journal of surfaces and colloids, 2009)
The confinement effect on the adsorption and reaction mechanism of unsaturated aliphatic, aromatic and heterocyclic compounds on H-ZSM-5 zeolite has been investigated by the four ONIOM methods (MP2:M06-2X), (MP2:B3LYP), (MP2:HF), and (MP2:UFF). The H-ZSM-5 'nanoreactor' porous intersection, where chemical reactions take place, is represented by a quantum cluster of 34 tetrahedral units. Ethene, benzene, ethylbenzene, and pyridine are chosen to represent reactions of various adsorbates of aliphatic, aromatic and heterocyclic compounds. Among the four combined methods, (MP2:M06-2X) outperforms the others. The results confirm that the method that takes weak interactions, especially the van der Waals interaction, into account is essential for describing the confinement effect from the zeolite framework. The effects of the infinite zeolitic framework on the cluster model are also included by a set of point charges generated by the embedded ONIOM model. The energies for the adsorption of ethene, benzene, ethylbenzene, and pyridine on H-ZSM-5 from an embedded ONIOM(MP2:M06-2X) calculation are predicted to be -14.0, -19.8, -24.7, and -48.4 kcal/mol, respectively, which are very close to available experimental observations. The adsorption energy of pyridine agrees well with the experiment data of -47.6 kcal/mol. We also applied the same computational methodology on the systematic investigation of the H/H exchange reaction of benzene and ethylbenzene with the acidic H-ZSM-5 zeolite. The H/H exchange reaction was found to take place in a single concerted step. The calculated apparent activation energies for benzene and ethylbenzene are 12.6 and 4.9 kcal/mol, which can be compared to the experimental estimates of 11.0 and 6.9 kcal/mol, respectively. The confinement effect of the extended zeolite framework has been clearly demonstrated not only to stabilize the adsorption complexes but also to improve their corresponding activation energies to approach the experimental benchmark